Kisah-kisah al-Qur’an (Qashash al-Qur’an) dalam Perspektif Pendidikan Islam - Afif, Muhammad Nur Hafidz; Widyaningrum, Ajeng (Lembaga Yasin AlSys, 2022)
This article aims to know the stories in the Qur'an from the perspective of Islamic education. This research is library research. From this study, it can be concluded that the stories in the Qur'an are an integral part of the content of the Qur'an. The stories in the Qur'an are stories about the ummah, events and, past events whose truth cannot be doubted. The stories in the Qur'an are various. The stories contained in the Qur'an are different from stories or fairy tales in general. This is because the characteristics that exist in the stories of the Qur'an are different from man-made stories or fables. The stories of the Qur'an are inseparable from the educational values contained in it. This aims to be an example (uswatun hasanah) and a lesson (ibrah) for mankind.